On the enhancement of the efficiency of concentrated solar power plants using nanofluids based on a linear silicone fluid and Pt nanoparticles - Juan Jesús Gallardo; Desireé De los Santos; Iván Carrillo-Berdugo; Rodrigo Alcántara; Javier Navas (Scientific Reports)
Abstract To reduce greenhouse emissions and producing electricity with the smallest environmental impact, developing solar power technology is one of the most important milestones to achieve. Thus, to improve the efficiency of the concentrated solar power (CSP) plants, with lower environmental impact, is of great interest. This work reports the development of nanofluids, a colloidal suspension of nanomaterials in a fluid, based on an environment-friendly base fluid for improving the performance of the heat transfer process in CSP plants. The nanofluids contain Pt nanoparticles in a linear silicone-based heat transfer fluid, and their stability is guaranteed for several weeks. Their properties of interest, density, surface tension, viscosity, isobaric specific heat and thermal conductivity were characterized to determine the performance of the nanofluids in solar thermal technology. Improvements of about 6% and 24% in specific heat and thermal conductivity were found, without significant increases in viscosity. In addition, their effect on the performance of collectors and heat exchangers in CSP using these nanofluids was analysed, and an enhancement of about 40% is found. Specific heat enhancements are also discussed in view of the strength of the interactions between methyl siloxane groups and low Miller index surfaces of Pt, with data from density functional theory simulations.